REVITALISASI MANAJEMEN WAKAF PRODUKTIF DI INDONESIA - Afandi, Moh. (Universitas Trunojoyo Madura, 2014)
AbstractReligious foundation is one of some alternative concepts of wealth distribution in Islam that has the most productivity more than other concept such as giving alms, bequest, inheritance, dying exhortation, even more than tithe concept with all it advantages. From prophet Muhammad era and also afterwards to this present time some countries that have realized religious foundation well and seriously able to fill their folks need in their overall aspects. They are Saudi Arabia, Egypt, Nation of Brunei and Malaysia. in Indonesia it always gets failure although considered that it’s conducted seriously, indeed up to now it likely can’t be felt the existence around society. By this library research writer wants to give some corrections and evaluations about religious foundation system in Indonesia with a great orientation just want to reestablish it. There are three obstacles in doing this concept here; the understanding of society about it productivity is not spread out yet, professionalism of NAZHIR (manager and management), and also the trust from society to government that always reduced more and more. For managing religious foundation with a great infestation and able to give the better alteration, so that, it’s needed five modals minimally; modal of legal, institutional and intellectual (thinker or conceptor), financial, social, and relational (either national or international connection). Key Word: Revitalization, Wakf, Productivity, Indonesia Wakaf merupakan salah satu alternatif dari berbagai konsep distribusi harta dalam Islam yang sudah terbukti paling produktif dari pada beberapa konsep yang lain, seperti shadaqah, infaq, hibah, wasiat, waris, bahkan dari pada konsep zakat pun infaq jauh lebih terbukti manfaatnya. Sejak masa Nabi dan beberapa masa setelahnya hingga sekarang beberapa Negara yang menerapkan wakaf dengan benar dan srius mampu menjawab kebutuhan rakyatnya dalam segala bidang. Negara-negara itu di antaranya Arab Saudi, Mesir, Brunai Darussalam dan Malaysia. Adapun di Indonesia sendiri meski sudah beberapa kali perwakafan mau digarap dengan srius, namun selalu saja gagal bahkan hingga sekarang belum terasa kehadirannya di tengah-tengah masyarakat. Melalui penelitian pustaka ini penulis memberikan koreksi dan mengevaluasi perjalanan perwakafan di Indonesia dengan tujuan ingin membangun kembali sistem perwakafan di Indonesia. Tercatat ada tiga kendala dalam pengelolaan wakaf di Indonesia, yaitu Pemahaman Masyarakat Tentang Wakaf Produktif belum merata, Profesionalisme Nazhir (pengelola wakaf dan manajeman yang digunakan), dan Kepercayaan Masyarakat Kepada Pemerintah yang kian menipis. Untuk mengelola wakaf dengan investasi yang melimpah dan bisa memberikan perubahan ke arah yang lebih baik, maka minimal membutuhkan 5 (lima) modal, yaitu; modal legal-institusional, Modal intelektual (pemikir dan penggagas), modal finansial (biaya), modal sosial (dukungan dari masyarakat), dan modal jaringan (kerjasama dengan berbagai macam lembaga baik nasional maupun internasional).